Peran Edukasi dalam Kepatuhan Penggunaan APD Penjamah Makanan Dapur dan Kantin RS - Hanifah Nurajizah; Wulandari Wulandari; Tika Noor Prastia; Fathimah Azzahra Muhammad; Aulia Aulia (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The use of Personal Protective Equipment (PPE) by food handlers is essential to prevent cross-contamination and ensure occupational safety in hospital food service settings. This study aimed to determine the effect of an educational program on improving knowledge and compliance with PPE use among food handlers in the Nutrition Unit Kitchen and Canteen of RSJ dr. H. Marzoeki Mahdi Bogor. The methods included direct observation, interviews, and educational activities delivered through counseling sessions, posters, and demonstrations of proper PPE use. Evaluation was conducted using pre-test and post-test assessments, followed by a 14-day monitoring period to observe behavioral changes. The results showed that knowledge scores in the Nutrition Unit Kitchen increased from 95.63% to 100% after the intervention, whereas the average score in the Canteen slightly decreased from 84.37% to 79.16%. PPE compliance after the education and monitoring reached 85%, with the highest improvements observed in the use of hair covers and aprons. Factors influencing compliance included PPE comfort, work habits, high ambient temperatures, and the level of supervision. Overall, the educational program proved effective in improving PPE-related practices and should be implemented regularly to support food safety within the hospital environment.